2020
DOI: 10.1038/s41598-020-65242-3
|View full text |Cite
|
Sign up to set email alerts
|

Propoxur resistance associated with insensitivity of acetylcholinesterase (AChE) in the housefly, Musca domestica (Diptera: Muscidae)

Abstract: Two unique housefly strains, PSS and N-PRS (near-isogenic line with the PSS), were used to clarify the mechanisms associated with propoxur resistance in the housefly, Musca domestica. The propoxurselected resistant (N-PRS) strain exhibited >1035-fold resistance to propoxur and 1.70-, 12.06-, 4.28-, 57.76-, and 57.54-fold cross-resistance to beta-cypermethrin, deltamethrin, bifenthrin, phoxim, and azamethiphos, respectively, compared to the susceptible (PSS) strain. We purified acetylcholinesterase (AChE) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
2
11
0
2
Order By: Relevance
“…Higher synergistic effects of PBO to propoxur in the N‐PRS were observed in our study, suggesting that the possibility of cytochrome P450‐based mechanism was associated with propoxur resistance. Nevertheless, the propoxur resistance in the N‐PRS could not be eliminated completely by PBO, which can be explained by the molecular target mutations and Mdace ‐mediated mechanism presented in the N‐PRS as previously described 7 …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Higher synergistic effects of PBO to propoxur in the N‐PRS were observed in our study, suggesting that the possibility of cytochrome P450‐based mechanism was associated with propoxur resistance. Nevertheless, the propoxur resistance in the N‐PRS could not be eliminated completely by PBO, which can be explained by the molecular target mutations and Mdace ‐mediated mechanism presented in the N‐PRS as previously described 7 …”
Section: Discussionmentioning
confidence: 79%
“…In a previous study, You et al . reported that the mutations and overexpression of Mdace were involved in the housefly propoxur resistance 7 . It has been identified there was an additional gene or genes other than one major factor involved in propoxur resistance 8 …”
Section: Introductionmentioning
confidence: 99%
“…В нескольких районах Китая отмечены высокие значения ПР комнатной мухи к пропоксуру (154-1000), в то время как в некоторых районах она была чувствительна к этому инсектициду (Wang et al, 2019). Отселектированная в лабораторных условиях раса (N-PRS) проявила >1035× устойчивость к пропоксуру и 1.7-, 12.1-, 4.3-, 57.8-и 57.5-кратную перекрестную устойчивость к бета-циперметрину, дельтаметрину, бифентрину, фоксиму и азаметифосу, соответственно, по сравнению с чувствительной расой (PSS) (You et al, 2020).…”
Section: резистентность к инсектицидам комнатной мухи в миреunclassified
“…Кроме того, уровень транскрипции и количество копий ДНК Mdace были значительно выше у устойчивой расы, чем у чувствительной. Таким образом, мутации в сочетании с повышенной экспрессией генов могут иметь важное значение для устойчивости комнатной мухи к пропоксуру (You et al, 2020).…”
Section: механизмы резистентностиunclassified
“…This in turn leaves the acetylcholine receptor permanently open, resulting in the death of the insect [10]. However, modi cation or mutation of the ace gene can change the structure of AChE, thereby reducing or eliminating the binding a nity of insecticides at the target-site and inducing the resistance to OPs and CBs[8, 12,13]. For house ies, there is only a single ace gene in the whole genome [14].…”
Section: Introductionmentioning
confidence: 99%